Biocatalysis and Biotransformation for Pharmaceuticals Synthesis - Ahmed Majeed, Atheer (International Journal of Psychosocial Rehabilitation, 2020)
The strategies of biological manipulation and biocatalysis for the synthesis of pharmaceuticals have risen in previous years. This review covers the following methods to candidate catalysis genes coding to enzymes in high expression to modify the microorganisms genetically. The operation will tend to create a new biotherapy used as catalysts for synthesizing a new assessable pharmaceutical product on both a laboratory and a commercial scale.